2022
DOI: 10.3389/fagro.2022.958498
|View full text |Cite
|
Sign up to set email alerts
|

Population fluctuation and distribution of bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) in soybean crops

Abstract: Studies on the spatiotemporal dynamics of crop pests enable the determination of their colonization pattern and dispersion in the landscape. Geostatistics is an efficient tool to determine the spatial distribution pattern of the pest in the crops and to visualize them in appropriate maps. Analysis of these maps across the crop developmental stages can be a helpful tool in precision agriculture programs. The aim of this study was to determine the spatiotemporal distribution of Bemisia tabaci whitefly adults and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Additionally, Domiciano et al (1993) noted that 20.29°C is a temperature that is conducive to an increase in thrips in Brazil. These findings concur with those of Rodrigues et al (2022), who discovered that between 30 and 50 days following the emergence of the soybean crop, adult and juvenile whitefly infestations began. Between 90 and 101 days after plant emergence, the maximum population density of ten adults per plant and two nymphs per leaf was reached.…”
Section: Seasonal Average Numbers Of the Main Insect Pests On Eggplan...supporting
confidence: 92%
“…Additionally, Domiciano et al (1993) noted that 20.29°C is a temperature that is conducive to an increase in thrips in Brazil. These findings concur with those of Rodrigues et al (2022), who discovered that between 30 and 50 days following the emergence of the soybean crop, adult and juvenile whitefly infestations began. Between 90 and 101 days after plant emergence, the maximum population density of ten adults per plant and two nymphs per leaf was reached.…”
Section: Seasonal Average Numbers Of the Main Insect Pests On Eggplan...supporting
confidence: 92%
“…c SDI calculated according to the formula C0/(C0 + C1) (Cambardella et al 1994). linked to this focus of aggregation (Bosco et al, 2020;Rodrigues et al, 2022;Zou et al, 2020). Pinho et al (2016) observed the relationship of the neighboring forest to the plantation with the emergence of R. palmarum infestations in oil palm, which presents similarity to E. cyparissias and causes drilling in palm trees.…”
Section: Focus In Forestmentioning
confidence: 99%